The Role of Family Education in the Formation of Adolescent Personality - Nurhidayati, Indah; Amin, Lailla Hidayatul; Hidayah, Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This literacy study investigates and analyzes the role of family education in adolescent character development. The aim of this research is to understand the contribution of home education to the development of adolescent character and values. Research methods include an in-depth literature review covering psychological theories of adolescent development and the concept of family education. The results of this study show that family education has a significant influence on adolescent personality development. Through daily interactions, the transmission of values, and the formation of family norms, adolescents internalize and develop their own identity. Factors such as family communication, parental involvement, and the formation of emotional bonds play an important role in shaping the psychological well-being of adolescents. Furthermore, this research emphasizes the importance of harmony between the values taught at home and the values applied in society. This balance plays an important role in helping teenagers overcome social pressures and develop strong personalities. These findings in practice mean the need to strengthen the role of family education through parent support programs and the development of family communication skills. This research contributes to the understanding of the important role of home education in adolescent personality development. Therefore, efforts to improve and strengthen education at home are expected to make a positive contribution to the development of the younger generation as a whole, preparing them to face life's challenges with confidence and integrity.